(untitled) - Day, Phyllis J (Boston, Mass., 1997)
Includes bibliographical references (p. 445-455) and index; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: United States -- Social policy; Public welfare -- United States -- History; Social policy; Phúc lợi công cộng -- Hoa Kỳ -- Lịch sử; Chính sách xã hội